The synergistic effect of rumen cellulolytic bacteria and activated carbon on thermophilic digestion of cornstalk. (October 2021) - Xie, Zhijie; Meng, Xianghui; Ding, Hongxia; Cao, Qin; Chen, Yichao; Liu, Xiaofeng; Li, Dong
Graphical abstract: Highlights: Adding AC and RCB simultaneously obtained the best methane production performance. Hydrogenispora, norank_o_MBA03, and Methanothermobacter were crucial for stalk AD. AC enriched cellulolytic Hydrogenispora and hydrogenotrophic Methanothermobacter . RCB increased cellulolytic Halocella and mixotrophic Methanosarcina . Co-existence of AC and RCB achieved higher cellulose degradation than adding alone. Abstract: To explore the bioaugmentation of rumen cellulolytic bacteria (RCB) and activated carbon (AC) on thermophilic digestion of cornstalk, biochemical methane potential tests were carried out. Adding RCB or AC can improve methane production, while simultaneous existence of AC (10 g/L) and RCB (5%) obtained the best performance. The maximum cellulose degradation rate, methane production rate and methane yield were 66.92%, 32.2 L/(kgVS·d), and 144.9 L/kgVS, which increased by 30.23%, 51.17%, and 20.35% compared with control group. The cellulolytic and fermentative bacteria ( Hydrogenispora ), syntrophic acetate-oxidizing bacteria ( norank_o_MBA03 ), and hydrogenotrophic Methanothermobacter were crucial for thermophilic digestion of cornstalk. The enhancement of AC was due to the enrichment of Hydrogenispora and Methanothermobacter, while RCB can increase the abundance of cellulolytic bacteria ( Halocella and norank_o_M55-D21 ) and mixotrophic Methanosarcina . The synergetic effect of AC and RCB owing to the enriched cellulolytic bacteria, the enhanced syntrophic acetate oxidation and the concentrated carbon metabolic flow to methane.